Buletin FPN Seremban 3 edisi 8 / UiTM, Fakulti Perakaunan UiTMCNS Kampus Seremban - UiTM, Fakulti Perakaunan UiTMCNS Kampus Seremban (Universiti Teknologi MARA, Negeri Sembilan, 2024)
I’m thrilled to present the 8th edition of the FPN Bulletin, a pivotal platform that not only fosters discussions but also shares invaluable insights, significantly shaping the accounting world. This issue delves into pivotal topics that are instrumental in shaping our current and future approaches to accounting. As educators, researchers, and practitioners, it's crucial for us to stay at the forefront of these ever-evolving subjects. Taxation, one of the most complex and influential areas of accounting, has a profound impact on both individuals and businesses. With new global tax regulations and the increasing use of e-invoicing systems, the understanding and teaching of taxation have never been more critical. It's imperative that future accountants are fully prepared to manage these complexities. We also delve into Financial Reporting, a field where standards are constantly evolving. In this edition, we explore consolidation— a key area that demands attention to maintain transparency and accuracy in financial statements. The field of Islamic Finance is rapidly growing, driven by principles rooted in ethics and Sharia compliance. It’s an important area for educators and practitioners to understand, especially as we prepare for a more diverse financial world. Additionally, we examine the economic performance of government-linked companies (GLCs) and compare the differences between the private and government sectors. This discussion offers fresh perspectives on how each operates. Financial Fraud remains a serious issue for organizations of all sizes. In this bulletin, we highlight different types of financial fraud and provide practical strategies to help you strengthen internal controls and foster a culture of integrity and accountability, empowering you to tackle this issue head-on.